Mesoporous shell@macroporous core aluminosilicates as sustainable nanocatalysts for direct N-alkylation of amines - Sekhar, Anandakumari C. Sunil; Ashokkumar, Anumol Erumpukuthickal; Cygnet, Choorapoikayil T.; Lakshmi, Saseendranpillai Vidhya; Deepak, Francis Leonard; Vinod, Chathakudath P. (Chemnanomat, 2018)
Aluminosilicate spheres with a macroporous core and mesoporous shell (Si/Al ratio of 11) is synthesised by a sol-gel method utilizing cetyltrimethyl ammonium bromide (CTAB) as a structure directing agent in basic medium. The selective incorporation of aluminium in the silica matrix results in the formation of aluminosilicates with an overall acidity of 0.32mmol/g with interconnected pores. Direct N-alkylation reaction is a prototype of C-N bond formation reaction and meso- macroporous aluminosilicate is shown to catalyze this reaction with excellent yield. The catalyst is tested and found sustainable for five catalytic cycles even without any high temperature regeneration step.
Keywords: Aluminosilicates; macroporous; Mesoporous; N-alkylation; nanocatalysis